[Acquitted ; Pulling out ; Life after basketball - Lazaro, Cheche (The Probe Team, 1990)
Tackles acquittal of Imelda Marcos from civil cases ; pull-out of U. S. Peace Corps from the Philippines after 29 years of service, and interviews with retired basketball players.